2014
DOI: 10.1002/ijch.201400095
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Unique Protonic and Hydrodynamic Behavior of Aqueous Solutions Confined in Extended Nanospaces

Abstract: A millimeter‐sized neural building block (NBB) shows high versatility to form a 3D heterogeneous neural component. A millimeter‐sized 3D neural network between heterogeneous neural tissues is established, and an efficient technique is then developed to observe the spatiotemporal metrological changes of single neuron in the NBB. This technique allows the visualization of axonal extension, dendritic branching, and morphological changes of presynaptic components and synapses in real time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…Therefore, the apparent activation energy (ΔE*) taken from the Arrhenius-type plots of 1 H-1/T1 values can be used as a measure for evaluating a potential energy for the motions of water accompanying with rearrangements of hydrogen bonds. The Arrhenius-type relation is expressed as follows: 8,31 1 1…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the apparent activation energy (ΔE*) taken from the Arrhenius-type plots of 1 H-1/T1 values can be used as a measure for evaluating a potential energy for the motions of water accompanying with rearrangements of hydrogen bonds. The Arrhenius-type relation is expressed as follows: 8,31 1 1…”
Section: Resultsmentioning
confidence: 99%
“…In order to enhance the performance of nanodevices, the structures and dynamics of liquids confined in nanospaces must be clearly understood, as nano-confinement can lead to changes in liquid properties, and strongly affects the behavior of target molecules and ions. [5][6][7][8] Over the past decades, the effects of confinement in mesoporous silica materials with 1 nm-scale spaces on microscopic properties of water molecules have been examined using experimental and theoretical methods. [9][10][11][12][13][14][15] These studies have clarified that the hydrogen bonding structures of water molecules near the pore surface are distorted and perturbed due to water-surface interactions or topological effects even at ambient temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…These specimens represent the smallest-ever square nanochannels formed on a fused silica substrate. Various previously proposed liquid models [ 1 , 2 ] suggest that 50 nm spaces will have a so-called proton transfer phase that exhibits different properties from the bulk liquid. In previous reports for liquids in 10 1 nm-sized channels using top-down fabricated nanofluidic devices, an electro-osmotic flow [ 40 ], water filling motions [ 42 ], introduction of fluorescent molecules [ 43 , 47 , 49 ] and electrical conductance [ 46 , 47 , 48 ] were observed.…”
Section: Resultsmentioning
confidence: 99%
“…In such nanospaces, chemical properties such as ion concentrations can become heterogeneous even when uniform in the bulk liquid. Our group previously reported that the properties of the liquid are also different in nanospaces compared with those in the bulk liquid [ 1 , 2 ]. Therefore, the unique aspects of nanospaces (small dimensions, extremely low volumes, very high surface-to-volume ratios and unique liquid properties) can be used to realize novel functional devices that are difficult to obtain using conventional bulk spaces.…”
Section: Introductionmentioning
confidence: 99%
“…Nanofluidics is much more than the scaling down of microfluidics, because fluids on this size scale exhibit specific characteristics that are not observed on the microscale or in bulk. For example, water confined in nanospaces has unusual structural and dynamical properties such as higher viscosity, lower dielectric constant and refractive index, or higher proton mobility, compared to those in bulk [ 4 ]. Other confinement-induced effects are observed in terms of hydrodynamic flow, conductivity, and ionic transport.…”
Section: Introductionmentioning
confidence: 99%